Posting Ulang Sebagai Jurnal Digital: Merekam Fase Emosional dan Identitas Gen Z di TikTok - Pratiwi, Dinda; Idrus, Nurul Ilmi (Universitas Muslim Maros, 2025)
This study explores the phenomenon of reposting on TikTok as a form of self-expression and digital identity construction among Generation Z (Gen Z). Although numerous studies have examined Gen Z’s engagement with social media, research focusing on the social functions and cultural meanings of TikTok’s repost feature remains limited. This study seeks to uncover how reposting serves as a medium for indirect communication, emotional regulation, and self-representation within the digital culture of contemporary society. The research employs a descriptive qualitative method with a phenomenological approach. Data were collected through in-depth interviews and observations involving 13 informants, consisting of nine women and four men aged between 18 and 25 who actively use TikTok’s repost feature. Informants were selected using purposive sampling, limited to users who had engaged with the feature within the past three months to ensure the contextual relevance and experiential accuracy. The findings reveal that reposting is motivated by various factors, including the desire for self-expression, indirect communication, sharing engaging content, and reflecting personal moods or life phases. The reposted content typically includes entertainment, educational, motivational, humorous, and emotionally relatable videos. This activity performs significant social functions such as reinforcing relationships, seeking emotional validation, and constructing a digital self-image. Positive impacts include emotional relief, a sense of calm, and enhanced social connectedness. However, negative effects were also identified, including misunderstandings, self-image distortion, and tendencies toward social media addiction. Viewed through Malinowski’s functionalist perspective, reposting represents a form of digital cultural adaptation that enables Gen Z to fulfil their psychological and social needs. TikTok, therefore, serves as a symbolic cultural space where emotions, relationships, and identities are continuously negotiated and expressed through digital means.